The Political Ecology of Protected Areas: The Case of Vatnajökull National Park - Feingold, Margo, 1992- (2021)
Protected areas are a key strategy to conserve nature. Their primary goal of a protected area is to conserve and manage biodiversity and natural resources in order to ensure their long-term ecological stability in the long-term. Historically, however, conservation efforts have been largely apolitical and have focused on nature first – commonly ignoring the human communities in or around a protected area and the impacts that a protected area can have on local communities. Political ecology has emerged as way to examine changes in environmental conservation while paying close attention to the social constructs, historical actors, and power relations that are involved in shaping environmental policy. The goal of this thesis was to explore the scholarship of political ecology and its contributions to critical analysis of executing conservation strategies and in particular protected areas and then, use the case of Vatnajökull National Park in Iceland to understand how this manifests in reality. Using a series of interviews with relevant stakeholders and multiple secondary sources related to the Vatnajökull National Park case, the study analyses the steps it takes to establish a national park and the power and political dimensions involved in the process. To ensure the long-term protection of an area, the historical, social, and political impacts need to be analyzed in order to enact long-lasting solutions. The case of Vatnajökull NP demonstrates that it is possible to effectively establish a protected area with these factors in mind, using a bottom-down, community-based conservation approach and political ecology offers a framework to examine the relationships between political, economic and social factors with environmental issues such when a protected area is being created or manage.